Analisis Model Pembelajaran Bilingual yang Efektif Untuk Siswa Sekolah Dasar di Indonesia - Setyaningrum, Riska; Asofah, Anisa; Cahyani, Bella Galih; Candra, Amelia Ellena; Firantinnur, Desva; Arahman, Devia Putri; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The real implementation in primary school learning activities has many kinds of learning models used by teachers, especially in improving foreign language learning (English) at school. The learning model that is often used to improve knowledge about English is the bilingual learning model. This study aims to analyze and identify bilingual learning models applied in primary school student learning in Indonesia. The method used in this research is a literature study with the type of research which is descriptive qualitative research. The researcher uses the literature study method to collect data on sources related to the research topic to be used. Then, the data that has been collected is then analyzed using a qualitative descriptive analysis method.The results showed that an effective bilingual learning model to be implemented in elementary schools is a model that not only supports the achievement of cognitive learning outcomes, but is also able to develop students' English and Indonesian language skills in a balanced manner. Inside-Outside Circle model, preview-review based on realia media, integrated skills learning, contextual learning assisted by visual media, and Talking Chips model are proven to increase students' active participation, speaking skills, and comprehension in two languages. Therefore, it is important for educational practitioners to choose an appropriate, integrated, and contextualized bilingual learning model in order to provide maximum impact in the learning process of students in elementary schools.